Outcomes of Outpatient Treatment for Primary Spontaneous Pneumothorax Using a Small-Bore Portable Thoracic Drainage Device - Karasaki, Takahiro; Shintomi, Shizuya; Nomura, Yukihiro; Tanaka, Nobutaka; Saito, Haruhisa; Yoshida, Yukihiro (The Thoracic and Cardiovascular Surgeon, 2014)
Background There is no consensus regarding the initial intervention for primary spontaneous pneumothorax. We report the outcomes of outpatient treatment for primary spontaneous pneumothorax using a portable thoracic drainage device.Patients and Methods Between April 2007 and December 2011, 99 consecutive patients with a first episode of primary spontaneous pneumothorax were indicated for insertion of a portable thoracic drainage device. All patients were treated with a small-bore portable thoracic drainage device that consists of a flexible 9F silicone catheter with one-way valves and a small plastic chamber. Successful treatment was defined as when the pneumothorax was resolved after the insertion of a portable thoracic drainage device solely on an outpatient basis. Demographic data and treatment outcomes were obtained by a retrospective chart review.Results Ninety-seven patients (98%) with a first primary spontaneous pneumothorax were discharged from the emergency department after insertion of a portable thoracic drainage device. Ninety-three patients (94%) resolved with outpatient treatment. The median duration of portable thoracic drainage device insertion was 4 days (range, 0–33 days). The recurrence rate after treatment with a portable thoracic drainage device was 34% (32/93). There were two infections (2.0%), two instances of hemothoraces (2.0%), and one severe discomfort at the insertion site (1.0%). There were no cases of tension pneumothorax or reexpansion edema.Conclusion Outpatient treatment for primary spontaneous pneumothorax using a portable thoracic drainage device had a high success rate with few serious complications and an acceptable recurrence rate.
Keywords: pneumothorax; quality of life; outcomes